Role of Case Studies Method in Food Policy Capacity Building - Babu, Suresh Chandra (2020)
Suresh Babu POLICY SEMINAR Virtual Event - Food Policy Research and Capacity Development in Eurasia Co-Organized by the Eurasian Center for Food Security (ECFS), World Bank Group, and IFPRI DEC 2, 2020 - 07:30 AM TO 09:00 AM EST